1999
DOI: 10.1080/01292989909359622
|View full text |Cite
|
Sign up to set email alerts
|

Market competition and media performance examining primetime series in Taiwan

Abstract: This paper studies the relationship between market competition and media performance in Taiwan. A close examination of the existing literature reveals that no conclusive findings have been published; some studies discovered positive relationships and others discovered contradictory ones. Using content diversity of TV programmes to represent media performance, this study analyzed the diversity among primetime series ran by the three TV stations in Taiwan. Three indicators were employed to measure diversity: dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Exposure diversity is the diversity of content as received by the audience.The rapid expansion of cable television in the 1990s has significantly increased source diversity, content diversity, and exposure diversity in Taiwan's television news. For example, recent studies conducted in Taiwan have shown that the growth of cable television has greatly increased the degree of competition in television, which in turn has resulted in more content diversity and greater freedom in news coverage (Li 1999;Wang and Lo 2000). A number of studies on television coverage of the election campaign have also demonstrated that the privately owned cable television channels are far more likely than the state-owned broadcast television stations to allot more coverage to the opposition candidates, to use the opposition parties' officials as news sources, and to offer more news coverage favorable to the opposition parties' candidates (Lo et al 1996(Lo et al , 1998(Lo et al , 2004.…”
Section: Media Diversity and Learning From Newsmentioning
confidence: 99%
“…Exposure diversity is the diversity of content as received by the audience.The rapid expansion of cable television in the 1990s has significantly increased source diversity, content diversity, and exposure diversity in Taiwan's television news. For example, recent studies conducted in Taiwan have shown that the growth of cable television has greatly increased the degree of competition in television, which in turn has resulted in more content diversity and greater freedom in news coverage (Li 1999;Wang and Lo 2000). A number of studies on television coverage of the election campaign have also demonstrated that the privately owned cable television channels are far more likely than the state-owned broadcast television stations to allot more coverage to the opposition candidates, to use the opposition parties' officials as news sources, and to offer more news coverage favorable to the opposition parties' candidates (Lo et al 1996(Lo et al , 1998(Lo et al , 2004.…”
Section: Media Diversity and Learning From Newsmentioning
confidence: 99%
“…The theory suggests that conglomeration is one of the core elements of an industry's market structure. Horizontal concentration is the most crucial factors as it derives to larger extend market's structure (Li & Chen, 2007). It implies that firms is similar or same business category are more likely to merge (Bashir & Fedorova, 2014).…”
Section: |mentioning
confidence: 99%
“…Most early studies found that increased competition within a market led to greater Downloaded by [Mount Allison University 0Libraries] at 05:58 06 October 2014 diversity and better quality in terms of mass media products (Atwater, 1984;Bae, 1999;De Jong & Bates, 1991;Everett & Everett, 1989;Grant, 1994;Hellman & Soramaki, 1994;Johnson & Wanta, 1993;Lacy, 1987Lacy, , 1988Lacy, , 1989Li, 1999;Litman, 1979;Powers, Kristjansdottir, & Sutton, 1994;Rogers & Woodbury, 1996;Wakshlag & Adams, 1985). For example, Chan-Olmsted (1996) found that the increased competition in commercial children's television in the United States led to the availability of more choices to young American audiences.…”
Section: Market Structure and Media Performancementioning
confidence: 99%